Implementasi Teknologi QR Code Dalam Pendaftaran Calon Mahasiswa Baru - Afdal Wahyu Prayuda; Achmad Aldi Sakoni; M. Arif Prayoga; Muhammad Said Hasibuan (Journal of Digital Literacy and Volunteering, 2023)
In tertiary institutions, the acceptance of new students (PMB) is an administrative procedure. Online registration forms are filled out by prospective students to complete the registration procedure. As a result, a system was created that makes use of QR Code technology, which is anticipated to make the registration process easier for potential new students (PMB). The system design approach that was utilized to create the design for the software requirements analysis system was the technique employed in this paper. In order to find out the processes that happen in a system based on the results of the Qr Code Design as a Service Optimization Media for New Student Admission Registration, researchers carry out software requirements in the design and construct optimization of new student admissions services.